ON THE TRAIL OF PARTICIPANT OBSERVATION IN TOURISM RESEARCH: A CONTRIBUTION BY - Marujo, Noémi (2022)
One of the greatest cultural attractions of the island of Madeira lies amid the exuberant landscape: the levadas (irrigation channels that run across the island for more than 2150 km and which constitute one of the richest features of the historical identity of the region). The levadas are considered a living monument of Madeiran culture (Fernandes, 2012); they are one of the attributes for promoting the destination and therefore attract many tourists (Marujo, 2013).